ANALISIS INOVASI TRANSPORTASI PUBLIK DARI PRAMBANAN EKSPRES MENJADI KERETA API LISTRIK (KRL) DALAM UPAYA MENINGKATKAN LAYANAN KEPADA MASYARAKAT JOGJA - SOLO - Pratama, Deviana Agustin Putri; Agustina, Dwi (Jurnal Ilmu Administrasi Publik, 2025)
PT. Kereta Api Indonesia (Persero) issued the latest intercity train, namely the KRL Commuter Line where this transportation operates to replace the Prambanan Express (Prameks) train in serving the Yogyakarta-Solo corridor which is called the KRL Commuter Line Jogja-Solo or KRL Joglo, or also called Lin Yogyakarta. This was done as an innovation from PT. Indonesian Railways (Persero) to improve services to the community. The increase in passengers is more because it is cleaner, more comfortable, on time, and the train is cooler compared to prameks. For ticket booking, it is also easier to KRL because you only need a card that is filled with a balance, unlike Prameks who have to book first using the application / have to queue at the counter. The purpose of this study is to analyze the innovation of public transportation from Prambanan Express to Electric Train (KRL) in an effort to improve services to the people of Jogja - Solo. The research approach uses a qualitative approach with a descriptive method. The determination of informants in this study uses purposive sampling techniques or purposeful sampling. From the results of the study, it is known that the innovation of public transportation from Prambanan Express to Electric Train (KRL) in an effort to improve services to the people of Jogja – Solo has been going well. There are several obstacles that occur both internally and externally. External obstacles such as the occurrence of fallen trees can be attempted with the precision of the officer giving directions to [there are passengers]. Internal obstacles such as the accumulation of passengers at the station, especially on every weekend, can be overcome with the addition of KRL cars. PT. Kereta Commuter Indonesia continues to improve the competence of its employees through various trainings held. Thus, the vision of PT. The Indonesian Commuter Train can be achieved, namely "Providing transparent and professional Public Information services".